1991
DOI: 10.1177/0013916591236007
|View full text |Cite
|
Sign up to set email alerts
|

Psychobiological Studies of Individuals in Small, Isolated Groups in the Antarctic and in Space Analogues

Abstract: Mental and physical health are both at risk under conditions of prolonged remoteness from home and removal from normal social support networks. This article examines relevant data from small groups isolated in (a) Antarctic summer stations, (b) a Transantarctic traverse expedition, and (c) a spacecraft simulator capsule.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 6 publications
1
17
0
Order By: Relevance
“…2000). A 4‐week Norwegian isolation study of group interaction and dynamics similarly found that initially participants experienced the team as positive and cheerful, followed by a period of dissatisfaction with group management and organization, before individual mood and team function stabilized in a positive manner 23 . Studies of depressive symptoms in US Antarctic winter expeditioners indicate that even clinically normal individuals experience an increase in depressive symptoms in high‐latitude environments during winter months and that these symptoms tend to peak mid‐winter 24 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2000). A 4‐week Norwegian isolation study of group interaction and dynamics similarly found that initially participants experienced the team as positive and cheerful, followed by a period of dissatisfaction with group management and organization, before individual mood and team function stabilized in a positive manner 23 . Studies of depressive symptoms in US Antarctic winter expeditioners indicate that even clinically normal individuals experience an increase in depressive symptoms in high‐latitude environments during winter months and that these symptoms tend to peak mid‐winter 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Some expeditions have more disharmony than others, either prior to the departure of the summer expeditioners or during the period of winter isolation. Individual psychological factors determine both the physical and psychological response of that individual 23 . Not all stressors are equally influential on all individuals, and individuals cope differently 26 .…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that the psychological reactions encountered during isolation follow the same sequential pattern, regardless of the environment (Gushin et al 1993;Ursin et al 1991). The first stage is anxiety, the second stage is depression and settling down to routine, the last, and most critical stage, seems to occur around the third quarter of the isolation period, and is characterized by emotional outbursts, aggressiveness (182) 1400 (174) 1525 (189) 1375 (183) 1712 (248) 1700 (168) 1250 (254) 1600 (138) II 1137 (124) 1332 (100) 1210 (36) 1500 (220) 1600 (137) 1637 (211) Sodium (mmol/24 h) I 232 (29) 245 (33) 289 (36) 244 (22) 227 (30) 254 (31) 194 (29) 280 (32) 269 (32) 281 (32) 242 (44) II 176 (35) 191 (12) 243 (24) 204 (16) 285 (3) 332 (60) Potassium (mmol/24 h) I 50.4 (8) 61 (6) 66 (10) 55 (10) 66 (12) 57 (5) 46 (6) 74 (7) 71 (9) 64 (5) 57 (5) II 62 (22) 61 (6) 51 (3) 54 (6) 71 (7) 84 (8) Nitrites (lmol/24 h) I 563 (56) 601 …”
Section: Discussionmentioning
confidence: 99%
“…In total, more than 150 questions were included in the questionnaire, of which a majority used a structured, closed-ended format. To study the impact of the design and use of tent shelters on users' well-being, some data collection techniques used by several studies of environmental psychology were adopted as a reference (Byrne, Barry, & Nelson, 1963;Derogatis, Lipman, Rickels, Uhlenhuth, & Covi, 1974;Leon, 1991;Mackay, Cox, Burrows, & Lazzerini, 1978;Ursin et al, 1991). These studies all used self-descriptive questionnaires as instruments to explore various aspects of psychological well-being such as mood, stress, depression, and anxiety.…”
Section: Methodsmentioning
confidence: 99%